Simulation of Optical Spectrum Code Division Multiple Access in Fibre to the Home Access Network - Othman, Maisara (2005)
Nowadays, the increasing number of end users accessing the Internet and taking advantage of today’s data transport capabilities has ignited an explosive demand for bandwidth. One of the next generation access systems that helps to improve this situation by pushing optical fibre closer to the home is called fibre-to-the-home (FTTH). FTTH offers virtually unlimited bandwidth to the subscriber with high splitting ratio, longer fibre span and provide the residential customers with bundled of high speed voice, data and video services.